Suhuang Antitussive Capsules-Ameliorative Effects on LPS-Induced Sputum Obstruction in Mice Through Promoting HGF Secretion - Tong, Xiyang; Liang, Rongyao; Jia, Yuning; Qin, Weiwei; Guo, Chao; Wu, Xingdong; Wang, Zhen; Chen, Dong; Tan, Ninghua (Frontiers in Pharmacology, 2019)
Sputum obstruction is one of common cough complications, which is tightly associated with airway inflammation. Suhuang antitussive Capsule (SH Capsule), a classic traditional Chinese medicine prescription, has been used for the treatment of post-cold cough and cough variant asthma in the long clinical application. This study aims to investigate the effects and underlying mechanisms of SH Capsule on LPS-induced sputum obstruction in mice. The results showed that SH Capsule effectively promoted the tracheal phenol red output and mucociliary clearance. SH Capsule also alleviated airway inflammation-mediated MUC5AC level through EGFR-ERK signaling. A further in vivo analysis showed that HGF inhibitor SU11274 abrogated the effects of SH Capsule on MUC5AC, well demonstrating that HGF was required for the beneficial effects of SH Capsule on expectoration in vivo. Moreover, SH Capsule promoted HGF secretion in a colon-dependent manner, which reached lung tissues via blood circulation. Collectively, this study provided new pharmacological data for clinical use of SH Capsule, and proposed a novel mechanism by which SH Capsule was pharmacologically promising for treating sputum obstruction.